(3SjGSI GdHOf haVjdI GdTQGH hefGaYg heVGQgs - (3eMeO Hf QSJe GdcjdGfi GdeJWHHs; (3SYOGddg GdHQOYjs ((3GdQTJ s)
(3ChdgG (B:s
(3gPG cJGH SjGSI GdHOf , haVjdI GdTQGH hefGaYg heVGQg , heGjJhdO ddecKQ efg , hjfaY Gdebd efg , heG jYGQV cd eG jYQV efg , aLejY TQhQ GdOfjG NeSI s
(3BNQgG (B:s
(3hef cGf GdZGdH Ydjg GdQWhHI ajchf eCchdg jYed ef dMhe GdUjO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GfXQg eY OSJhQ GdeHJOjf Qbe (B" 464"s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B120 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B329 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs